2020
DOI: 10.1002/rcs.2091
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience of single‐incision robotic colorectal surgery with da Vinci SP platform

Abstract: Background: The da Vinci Surgical System (Intuitive Surgical, Sunnyvale, CA) was introduced to overcome the limitations of single-incision laparoscopic surgery, which is challenging due to its restrictions regarding triangulation and retraction. The purpose of this article is to describe the initial experience with single-incision surgery using the da Vinvci Single-Port Platform (dVSP). Methods:The medical records of patients with colorectal disease, who underwent single-incision robotic surgery using the dVSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…However, this study was performed on the da Vinci Si ® platform (Intuitive Surgical Inc, Sunnyvale, CA), not on the new da Vinci SP ® robotic system. Only a few papers with a very small number of cases have shown that the new da Vinci SP ® robotic system was safe and feasible for right hemicolectomy 19–21 . However, no studies have compared the new da Vinci SP ® robot with SPL right hemicolectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was performed on the da Vinci Si ® platform (Intuitive Surgical Inc, Sunnyvale, CA), not on the new da Vinci SP ® robotic system. Only a few papers with a very small number of cases have shown that the new da Vinci SP ® robotic system was safe and feasible for right hemicolectomy 19–21 . However, no studies have compared the new da Vinci SP ® robot with SPL right hemicolectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few papers with a very small number of cases have shown that the new da Vinci SP ® robotic system was safe and feasible for right hemicolectomy. [19][20][21] However, no studies have compared the new da Vinci SP ® robot with SPL right hemicolectomy. Therefore, this study is meaningful in that it included quite a lot of data, with a total of 41 SPR right colectomy cases, and compared SPL and SPR.…”
Section: Discussionmentioning
confidence: 99%
“…These advantag-es provide high dexterity, especially in the field of transanal, transoral, and transabdominal surgery. Noh et al [26] reported the feasible and safe initial experience of single-port and reduced-port robotic surgery using the single-port da Vinci system for right-and left-sided colorectal resection. Future studies are needed to demonstrate the true benefits of various kinds of single-port and reduced-port accesses with laparoscopic and robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These multiarticulating instruments and endoscope could minimize the collision in a single-incision colorectal surgery. For its use in colorectal surgery, several reports showed its performance and validity during colectomy and total mesorectal excision [ 4 , 6 8 ]. In the present report, we present our experience of RHC with extended lymphadenectomy using dVSP.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation, Intuitive Surgical (Sunnyvale, CA, USA) launched the da Vinci SP surgical system (dVSP) in 2018, which was developed to perform robotic single-incision surgery. Since we reported the first use of dVSP in colorectal surgery, many institutions adopted this system and its use has been increasing [ 4 ]. And, in accordance with the increment of adoption of dVSP, the indication to apply this platform has been expanding.…”
Section: Introductionmentioning
confidence: 99%